Military Coup in Myanmar and Idea Of Security Sector Reform - Jonah Silas; Shinta Ressmy (International Journal of Social Sciences Review, 2021)
This paper will describe the need and obligation of a State to carry out Security Sector Reform on the concept of civil and military relations by taking the example of the military coup that is currently taking place in Myanmar in 2021. It aims to obtain an overview of the efforts made by military groups in Myanmar that carried out the coup. Against civilian government, which is not the first time this has happened in Myanmar. Using Huntington’s approach to Civilian Control, military professionalism can be formed if civilian supremacy has been built. Edmunds’ presentation on Security Sector Reform can run if democratization has been implemented in a country. Public resistance to the Min Aung Hlain Military Junta government is a form of support for the idea of democratization promoted by the NLD in Myanmar.